Laparoscopic treatment of a series of rare tumors, gastric schwannoma with chronic iron deficiency anemia: A case report. (December 2021) - Zhou, Xinyuan; Lu, Ni; Wang, Chen
Abstract: Introduction and importance: Gastric schwannoma is a rare and slow-growing gastrointestinal mesenchymal tumor. Gastric neurilemmoma accounts for less than 1% of all gastric tumors. Without specific clinical manifestations, it is easy to be misdiagnosed before the operation, and rupture and bleeding will lead to persistent anemia in patients. The diagnosis can only be confirmed by pathological examination. Case presentation: A 55-year-old woman was admitted to The Second Hospital of Lanzhou University due to abdominal distension, pain, acid regurgitation, and belching. The tumor was completely removed by laparoscopy. The postoperative specimens were diagnosed as gastric neurilemmoma by pathological examination. Clinical discussion: Schwannoma is a benign neurogenic tumor. Complete surgical resection with a negative cutting edge is an effective method for the treatment of gastric schwannoma. Because the lesion is benign, the prognosis of the patient is good. Conclusion: Laparoscopic tumor resection is a choice for the treatment of gastric schwannoma, and the therapeutic effect is good. Highlights: This study reports a rare 55-year-old woman with gastric iron deficiency anemia with schwannoma, which was confirmed by laparoscopy and finally pathologically. This case report shows that although gastric schwannoma has no specific clinical manifestations of the digestive tract, it can cause chronic iron deficiency anemia in patients Our successful cases show that laparoscopic surgery to remove tumors is an option for the treatment of this disease.